DIFFERENTIATED EDUCATION AND COMMUNITY-BASED TOURISM IN THE CAIÇARA TERRITORIES OF PARATY (RJ) - BARROS,ANDRÉ LOUREIRO RIBEIRO DE (2019)
Abstract The schools of caiçaras communities in “Praia do sono” and “Pouso da Cajaíba”, located in Paraty (RJ), initiated in 2016 to offer middle school education with the purpose of an education adapted to their realities. This initiative happens in a period when the communities are seeking new ways to develop tourism. The present article aims to discuss the construction process of the differentiated school education and its contribution to the development of tourism. In addition to the research of bibliographic references and secondary data, there was participation in events related to the theme and the implementation completion/execution of semi-structured interviews with representatives that have been discussing the curricular proposal and its impacts in the territory. The research shows that the process that is being proposed by means of the differentiated education can contribute to the organization of the community-based tourism, focused in questions such as autonomy and belonging.